Anti-Influenza A Virus Activity of Rhododendron brachycarpum Extract and Identification of Hyperoside as the Active Constituent - Yung Hun Park; Soo Yong Shin; Hayeong Choi; Jae Hyeok Lee; You Jin Kim; Seong Ji Woo; Wonkyun Ronny Im; Sung Ho Jeon (Microbiology Research)
Influenza A virus (IAV) poses significant public health challenges due to its rapid mutation and drug resistance, necessitating novel antiviral strategies. Rhododendron brachycarpum, traditionally employed in folk medicine to treat inflammatory conditions, contains bioactive flavonoids with potential antiviral effects. In this study, we investigated the anti-influenza activity of R. brachycarpum leaf extract and identified hyperoside (quercetin-3-O-galactoside) as the active constituent. The crude extract and its n-butanol fraction markedly reduced IAV replication in Madin–Darby canine kidney (MDCK) cells, with IC50/CC50 values of 74.51/201.09 μg/mL and 24.5/113.1 μg/mL, respectively. Hyperoside, purified via bioactivity-guided fractionation and HPLC analysis, demonstrated potent antiviral activity, with an IC50 of 66.59 μM (30.92 μg/mL) and a CC50 of 318.9 μM (148.1 μg/mL), indicating a favorable selectivity index. It significantly suppressed viral mRNA and protein expression in infected cells. Time-of-addition and hemagglutination inhibition assays suggested that hyperoside exerts antiviral effects during early infection stages, likely interfering with viral entry. In silico molecular docking analysis further supported this mechanism, revealing that hyperoside binds strongly to the receptor-binding domain of hemagglutinin (−11.5 kcal/mol), potentially blocking viral attachment. These findings reveal that hyperoside is a major antiviral component of R. brachycarpum and underscore its therapeutic potential as a natural antiviral candidate against IAV infections.